2013
DOI: 10.1007/s10964-013-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and Peer Relationships Among Caucasian, Hispanic, Asian, and African American Adolescents

Abstract: Past research has shown that locus of control plays an important role in a wide range of behaviors, such as academic achievement and positive social behaviors. However, little is known about whether locus of control plays the same role in minority adolescents' peer relationships. The current study examined ethnic differences in the associations between locus of control and peer relationships in early adolescence using samples from the Early Childhood Longitudinal Study (ECLS-K: 5,612 Caucasian, 1,562 Hispanic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
1
17
0
3
Order By: Relevance
“…The measure has been frequently used in educational settings due to its briefness and efficiency. Previous research has demonstrated that the scale has good internal consistency (e.g., Cronbach's a = .75 in Tourangeau, Nord, Lê, Sorongon, & Najarian, 2009; Cronbach's a = .75 in Kang, Chang, Chen, & Greenberger, 2015). Similarly, the locus of control measure had good internal consistency in this sample (Cronbach's a = .75).…”
Section: Methodssupporting
confidence: 50%
“…The measure has been frequently used in educational settings due to its briefness and efficiency. Previous research has demonstrated that the scale has good internal consistency (e.g., Cronbach's a = .75 in Tourangeau, Nord, Lê, Sorongon, & Najarian, 2009; Cronbach's a = .75 in Kang, Chang, Chen, & Greenberger, 2015). Similarly, the locus of control measure had good internal consistency in this sample (Cronbach's a = .75).…”
Section: Methodssupporting
confidence: 50%
“…In addition, it is associated with well-being and a more positive psychological adaption (Shapiro, Schwartz, & Astin, 1996). College students with an internal locus of control report feeling more accepted than those with an external locus of control (Kang, Chang, Chen, & Greenberger, 2015).…”
Section: Locus Of Controlmentioning
confidence: 99%
“…These findings also provide support for the role of PC in understanding vocational expectations of ethnic minority youth. The fact that PI may be an effective way to enhance perceptions of control is promising, given that previous research suggests promoting a sense of PC can be a complex agenda with ethnic minority youth in particular (Kang et al, 2015). This may be the case because ethnic minority youth are more likely to encounter systemic oppression that influences their assessments of being in control of their destinies (Threlfall et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PC might be important to examine because youth who believe that factors such as luck are more powerful determinants of the future than are one's own actions may also be less likely to feel confident in their vision for their vocational success. Some research has found that in ethnic minority populations, PC is a less consistent predictor of a variety of educational and mental health outcomes (Kang, Chang, Chen, & Greenberger, 2015). This may be because experiences of racism and oppression can result in ethnic minority youth feeling like they have less control over their destinies than do their ethnic majority counterparts (Threlfall et al, 2013).…”
Section: Individual Variable Mechanismsmentioning
confidence: 99%